Landscape gardening art in aesthetic sphere of information society - Мокляк, Л. І. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The aesthetic analysis of the place and role of the landscape art in the system of spiritual values of the modern information society is represented in the article.